2017
DOI: 10.1016/j.bone.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral bone marrow fat, bone mineral density and diabetes: The Osteoporotic Fractures in Men (MrOS) study

Abstract: Elevated vertebral bone marrow fat (BMF) among individuals with osteoporosis has been established in histomorphometric studies. Several studies have found a negative correlation between BMF and bone mineral density (BMD) at the spine in men and women across different age groups. Animal studies have also observed bone loss with increased BMF in mice with induced diabetes. Our study objective was to test the hypothesis that the association between BMF and BMD varies by diabetic status. We performed a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 49 publications
2
44
2
Order By: Relevance
“…Men with diabetes had a higher bone marrow fat fraction compared to nondiabetic men. The correlation between bone marrow fat fraction and BMD differed by diabetes status . With regard to fatty acid composition, a lower fat unsaturation in bone marrow fat was found in diabetic women compared to nondiabetic women .…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 84%
See 1 more Smart Citation
“…Men with diabetes had a higher bone marrow fat fraction compared to nondiabetic men. The correlation between bone marrow fat fraction and BMD differed by diabetes status . With regard to fatty acid composition, a lower fat unsaturation in bone marrow fat was found in diabetic women compared to nondiabetic women .…”
Section: Applications Of Quantitative Bone Marrow Mri and Mrsmentioning
confidence: 84%
“…The correlation between bone marrow fat fraction and BMD differed by diabetes status. 120 With regard to fatty acid composition, a lower fat unsaturation in bone marrow fat was found in diabetic women compared to nondiabetic women. 121 In women with anorexia nervosa, Bredella et al were able to demonstrate a paradoxical increase in bone marrow fat measured via single-voxel MRS, with higher fat fraction in anorectic women compared to healthy controls.…”
Section: Metabolic Diseasesmentioning
confidence: 97%
“…Both the amount and composition of bone marrow fat appear to be altered in diabetes. In the MrOS study, diabetic men had higher bone marrow fat as compared with nondiabetic men . With regard to bone marrow fat composition, T2D postmenopausal women with fragility fractures had higher saturated bone marrow fat and lower unsaturated bone marrow fat as compared with nondiabetic controls and to T2D without fractures .…”
Section: Mechanisms For Deficits In Diabetic Bonementioning
confidence: 93%
“…42 Men with diabetes have higher BMF that matches non-diabetic patients. 43 Marrow adipocyte proliferation at the expense of osteoblast differentiation may explain increased bone weakness and a lack of bone increase observed in the pioglitazone compared with placebo arm in the present study. Beck et al 44 elegantly showed that TZD treatment of patients with T2DM for 6 months inhibits the commitment of primary human bone marrow stromal cells from osteoblasts to adipocytes.…”
Section: Discussionmentioning
confidence: 59%